Managing Value Co-Creation in Digitalization: The Role of Consumer’s Ethical Perception and Islamic Relationship Quality - Dita Prameswari; Fariha Azzahra (LPPM Universitas An Nuur, 2023)
Background: The world is currently controlled by a digital technology system which can influence people's lifestyles as consumers. Thus, business people in particular need to create a value that is useful for the progress of their business so that this research refers to increase value co-creation. Purpose: This research aims to increase a collaborative value (value co-creation) between companies and their customers so that they are able to create something new and useful for both parties by using the variable consumer's ethical perception, relationship quality in the Islamic concept. Methods: The research method used is content analysis method and literature survey to define concepts and develop measurements. Results: The results of the study have found a construct in an effort to increase value co-creation, namely the new concept of relationship quality in Islamic concept and consumer’s ethical perception. Conclusion: Islamic relationship quality is believed to make it easier for a company to maintain the quality of communication in the long term and to be able to make creative ideas as a form of collaborative innovation between companies and consumers. Therefore, in the long term it is hoped that it will increase the value of co-creation. Suggestion: For the future agenda we plan to validate the measurement of both concepts and test the proposed model with quantitative methods.